High value utilization method of plant oil hydrated oil foots - WANG WEIFEI; YUAN DONGJUAN; WANG YONGHUA; LI ZHIGANG; WANG FANGHUA; YANG BO (2015)
The invention discloses a high value utilization method of plant oil hydrated oil foots, which comprises the following steps: 1)adjusting temperature of oil foots hydration to 40-65 DEG C, adding lipase or phosphatidase, stirring and reacting until an acetone insoluble substance in a system enable 20-45% of weight reduction; and 2)centrifuging or standing and separating to obtain a light phase taking oil as a main component and a heavy phase containing modified phosphatide. The method makes appropriate hydrolysis on hydrated oil foots by lipase or phosphatidase, then through separation, the light phase taking oil as the main component and the heavy phase containing modified phosphatide can be obtained, and oil and modified phosphatide have high value. The method can realize high value utilization of plant oil hydrated oil foots.